Recent advancements to measure membrane mechanical and transport properties. (2nd January 2022) - Has, Chandra
Abstract: The natural vesicles, microscopic spherical structures defined by a single or many lipid bilayer membranes, not only entrap but are also dispersed in the aqueous environment. The space division between inner and outer compartments is also the basic characteristics of cell membranes playing several essential functions in all living organisms. Thus, vesicles are a simple model system for studying various cellular properties. In the last few decades, synthetic vesicles (or liposomes) have gained substantial popularity from many academia as model membranes and from many pharmaceutical industries as targeted and controlled drug delivery systems. The manufacturing of vesicles with desired characteristics that can entrap and release the drugs as required is one of the major challenges in this research area. To this end, a better understanding of the mechanical and transport properties of vesicles is essential to gain deeper insight into the fundamental biological mechanisms of vesicle formation and cellular uptake. The requirement has brought the modifications in membrane composition (with cholesterol, charged lipid, proteins, peptides, polymers, etc.) and solution conditions (with salts, pH, buffers, etc.). This article mainly focuses on the different techniques developed for studying the mechanical and transport properties of natural/synthetic vesicles. In particular, I thoroughly review the properties such as bending and stretching elastic moduli, lysis tension, and permeability of vesicle membranes.